PENGARUH SIZE, GROWTH, PROFITABILITAS, STRUKTUR MODAL, KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Meidiawati, Karina; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The firm value shows that the prosperity of stakeholders will increase, if the stock price is increased as well. The firm value becomes very important because it reflects the performance of the company which can influence the perception of investors to the company. This research is meant to find out the influence of firm size, the growth of the company, profitability, capital structure, and dividend policy to the firm value. The samples are 21 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) during the 2010-2014 periods and they have been selected by using purposive sampling. The statistic test instrument uses SPSS 22 version which is carried out to perform classic assumption test, multiple linear regressions analysis, and the hypothesis test. Based on the result of normality test, multicolinearity test, heteroscedasticity, and autocorrelation, some variables that deviate from the classic assumption have not been found. The result of the hypothesis test shows that: (1) firm size does not have any influence to the firm value; (2) the growth of the company does not have any influence to the firm value; (3) Profitability does not have any influence to the firm value; (4) capital structure does not have any influence to the firm value; (5) dividend policy does not have any influence to the firm value.Keywords: Total Assets, Profitability, Capital Structure, Dividend Policy, Firm Value.